A imagem do índio na câmera do vídeo: o efêmero e o mosaico no cruzamento do índio com o não índio, durante a produção documentária “Xingu” em 1984 e 2006, no Parque Nacional do Xingu - Garcia, Orlando (2017)
We develop here an analysis of the relations between some groups of Indians of the Xingu and the production of a documentary series made on these same Indians by the journalist Washington Novaes in 1984 and in 2006, with the titles: Xingu - The Magical Land and Xingu - Earth Endangered , whose films we have as object of study. Our intention is to point out the possible way to break with the construction of preconceived ideas about a supposed "identity purism" in the life of the Indian, which developed in two ways: by the image that was built historically on it, aiming at the maintenance of a pretended Indian identity through the "preservation of a primitive culture" that certainly does not exist anymore, like that which existed in the sixteenth century, and through a discourse that puts it in the condition of acculturated and disappearing, from the absorption of elements of non-Indian culture. If we do not agree with either position, we present a third one, which places it as having developed historically and socially, merging with non-Indian culture through peaceful and violent encounters, but without prejudice to its degradation or of his disappearance as a people. The series of documentaries produced by Washington Novaes brings in a strong criticism to the introduction of non-Indian elements in their culture, and defends about them, as if it were possible, the maintenance of an archaic and primitive cultural life, as the only way to prevent their total "disappearance" as an identity group. In this context, we propose to subvert the ideas of this "identity purism", supporting us in the theoretical formulations related to the field of communication, anthropology and historiography. As a result of this, we have obtained, from the analysis of the texts on Amerindian perspectivism and others, a theoretical support to question the points of view quoted above. We analyze the associations between these groups of Indians in the region with the technologies and tools introduced in the villages, their connections with the feast of Kuarup and with the shamanism, in order to show the possible ways to break with the construction of ideas around the identity conception of the Xingu Indians